Causes, consequences, and cures of myopic loss aversion: An experimental investigation - Gerlinde Fellner; Matthias Sutter (University of Bonn, Bonn Graduate School of Economics (BGSE), 2005)
Myopic loss aversion (MLA) has been established as one prominent explanation for the equity premium puzzle. In this paper we address two issues related to the effects of MLA on risky investment decisions. First, we assess the relative impact of feedback frequency and investment flexibility (via the investment horizon) on risky investments. Second, given that we observe higher investments with a longer investment horizon, we examine conditions under which investors might endogenously opt for a longer investment horizon in order to avoid the negative effects of MLA on investments. We find in our experimental study that investment flexibility seems to be at least as relevant as feedback frequency for the effects of myopic loss aversion. When subjects are given the choice to opt for a long or short investment horizon, there is no clear preference for either. Yet, if subjects face a default horizon (either long or short), there is rather little switching from the one to the other horizon, showing that a default might work to attenuate the effects of MLA. However, if subjects switch, they are more often willing to switch from the long to the short horizon than vice versa, suggesting a preference for higher investment flexibility.
Keywords: G11; D80; C91; 330; loss aversion; risk; investment; experiment; Anlageverhalten; Risikoaversion; Experiment; Informationsverhalten; Theorie; equity premium puzzle